Politics of Active Representation: The Trade-off Between Organizational Role and Active Representation - Yun, Changgeun (Review of Public Personnel Administration, 2020)
The translation of passive into active representation assumes that bureaucrats are willing to serve the interest of their social group when developing and implementing policies. However, the assumption does not account for organizational socialization—the process of being taught what is important in an organization. In addition, there is a comparative paucity of theoretical and conceptual frameworks to explain why and how bureaucrats decide to become active representatives. In this study, I develop a framework for analyzing the decision to engage in active representation. The framework recognizes that active representation conflicts with organizational role and is based on the assumption of public choice theory that humans are utility maximizers. Bureaucrats are not totally devoted to active representation, but instead find an optimal point at which their self-interest is maximized in interrole conflict.
Keywords: active representation; inter-role conflict; organizational socialization; self-interest maximization